(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the problem of the origin of the oikonym Severodonetsk is investigated, the motive of the nomination of the name of the river Siverskiy Donets, the succession and the gradualness of its appearance, the correspondence of the derived oikonym to the forming hydronym both structurally and semantically are defined, and also the initial etymological base – ethnonym siveryani is analyzed.